Weld Characteristics and NC Bending Formability of QSTE340 Welded Tube - 任宁 詹梅 杨合 秦亚涛 张志勇 蒋浩民 刁可山 陈新平 (Transactions of Tianjin University, 2011)
The mechanical characteristics of the weld joint were investigated by tensile test, microstructure test, and microhardness test. The welded tube NC bending tests were carried out to evaluate the weld on the formability of the QSTE340 welded tube. The results show that the wall thinning degree, cross-sectional deformation and springback angle increase significantly as the weld line is located on the outside of the bend compared with that located on the middle and inside, and the welded tubes produce nearly identical performance as the weld line is located on the middle and inside. The wall thickening degree decreases much as the weld line is located on the inside of the bend. So the welded tube can acquire good bending formability as the weld line is located in the region away from the outside of the bend.